(untitled) (Universal International Scientific Journal, 2026)
This article highlights the role of parents in raising children in the formation of a mature personality, relying on artistic and spiritual literature. It also analyzes the impact of gender stereotypes on children’s minds, social imagination and value systems from a scientific and psychological perspective. The need to raise a child spiritually through the family environment, national heritage and literary sources is substantiated.